2014
DOI: 10.1111/bdi.12278
|View full text |Cite
|
Sign up to set email alerts
|

Age‐associated alterations in corpus callosum white matter integrity in bipolar disorder assessed using probabilistic tractography

Abstract: Objectives Atypical age-associated changes in white matter integrity may play a role in the neurobiology of bipolar disorder, but no studies have examined the major white matter tracts using nonlinear statistical modeling across a wide age range in this disorder. The goal of this study was to identify possible deviations in the typical pattern of age-associated changes in white matter integrity in patients with bipolar disorder across the age range of 9 to 62 years. Methods Diffusion tensor imaging was perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 57 publications
2
18
0
Order By: Relevance
“…However, none of the aforementioned studies employed deterministic tractography. Indeed, regardless the limited evidence of tractography, the few existing studies support our findings (Emsell et al, 2013;Sarrazin et al, 2014;Toteja et al, 2014). However, technical limitations of previous DTI studies might account for the lack of evidence involving the fornix, as acknowledged by more recent investigations (Emsell et al, 2013).…”
Section: Discussionsupporting
confidence: 56%
See 3 more Smart Citations
“…However, none of the aforementioned studies employed deterministic tractography. Indeed, regardless the limited evidence of tractography, the few existing studies support our findings (Emsell et al, 2013;Sarrazin et al, 2014;Toteja et al, 2014). However, technical limitations of previous DTI studies might account for the lack of evidence involving the fornix, as acknowledged by more recent investigations (Emsell et al, 2013).…”
Section: Discussionsupporting
confidence: 56%
“…However, the fornix WM microstructure has been less frequently examined. The existing results were controversial, showing no major structural changes in this region in BD (al., 2008;Barysheva et al, 2013), but also FA changes in the fornix in BD ( Barnea-Goraly et al, 2009;Oertel-Knochel et al, 2014). However, none of the aforementioned studies employed deterministic tractography.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One recent cross-sectional study, using probabilistic tractography, reported a stronger negative association between age and WM integrity in the corpus callosum of BD patients than HCs (11). However, other studies have found no evidence of differential age associations with WM integrity (12), though small sample sizes and short follow-up periods may have limited the statistical power.…”
Section: Objectivementioning
confidence: 99%